Synthesis method of silicon dioxide microsphere filler for fluororubber and fluororubber filled and modified by silicon dioxide microsphere filler

Silica microspheres synthesized by microwave mixing-stober method are blended with fluoroelastomer as fillers to form FKM/SiO2 composite material, which solves the problems of insufficient mechanical properties, thermal properties and wear resistance of fluoroelastomer and significantly improves the composite material performance.

CN119430197APending Publication Date: 2025-02-14INST OF NEW MATERIALS & IND TECH WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411351638.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing fluoroelastomer has problems with insufficient mechanical properties, thermal properties and wear resistance during use, especially due to the small particle size and high surface energy of the silica microspheres, the poor matrix compatibility and weak filler-matrix interface connections. .

Method used

Silica microspheres were synthesized by microwave mixing-stober method, and the prepared microspheres had a particle size of about 15-20nm. They were prepared as mechanical blending with fluoroelastomer to form FKM/SiO2 composite material.

Benefits of technology

The mechanical properties, thermal properties and wear resistance of fluoroelastic composites have been significantly improved, and the tensile strength of FKM/SiO2 composites has been increased by 115%, and the thermal decomposition temperature and carbon residual rate of the composites have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430197A_ABST
    Figure CN119430197A_ABST
Patent Text Reader

Abstract

The invention provides a synthesis method of a silicon dioxide microsphere filler for fluororubber and fluororubber filled with the silicon dioxide microsphere filler, a microwave mixing-stober method is adopted to synthesize silicon dioxide microspheres serving as the fluororubber filler, the particle size of the prepared microspheres is about 15-20 nm, and after the filler is compounded with FKM, an FKM / SiO2 composite material is prepared; tests show that the filler in the FKM / SiO2 composite material is small in particle size and good in dispersity, the filler can be well combined with a matrix, the mechanical property of the FKM is remarkably improved, and compared with the original FKM, the tensile strength of the FKM / SiO2 composite material is remarkably improved (22 MPa, improved by 115%); in conclusion, the silicon dioxide microspheres synthesized by the microwave mixing-stober method have wide application prospects in the field of high-performance FKM materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer material technology and rubber preparation, in particular to a method for synthesizing silicon dioxide microsphere filler for fluororubber and the filled modified fluororubber. Background Art

[0002] Fluororubber (FKM) has good resistance to acid and alkali media, aging and high temperature, and is widely used in the fields of automobiles, chemicals, ships, oil extraction, aerospace, national defense, and high-precision instruments. In order to meet the performance requirements of FKM under specific working conditions, FKM is usually combined with various compounding agents, such as reinforcing agents, softening plasticizers, and anti-aging agents. Carbon black, as an amorphous carbon nano-reinforcement particle, is widely used to improve the elastic modulus and mechanical properties of fluororubber, but it will cause serious environmental pollution during use.

[0003] Silicon dioxide (SiO2) is a rich resource in the earth's crust with good biocompatibility and huge development potential. At present, silicon dioxide has been used in many fields such as adsorption, biomedicine and energy storage. According to the microscopic morphology, silicon dioxide can be divided into spherical, rod-shaped, mesoporous structure, mesoporous hollow structure and dendrite structure.

[0004] Commercial silica microspheres have small particle size, large specific surface area and high surface energy, which makes them easy to agglomerate in the fluororubber matrix. At the same time, because silica microspheres contain a large number of silanol groups and show strong hydrophilicity and oleophobicity, they have poor matrix compatibility and weak filler-matrix interface connection, which is not conducive to the mechanical properties, thermal properties and wear resistance of the composite material, thus limiting its application. Therefore, the mechanical properties, thermal resistance and wear resistance of FKM composites can be improved from the perspective of improving silica microsphere fillers. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for synthesizing silica microsphere filler for fluororubber and the filled modified fluororubber. The technical scheme adopted by the present invention is as follows:

[0006] In a first aspect, a method for synthesizing a silica microsphere filler for fluororubber is provided. The method for preparing the silica microsphere filler comprises: dissolving NH3H2O ​​in ethanol and stirring evenly, then adding tetraethyl silicate and mixing by microwave to obtain a sol, and drying the obtained sol to obtain the silica microsphere filler.

[0007] Furthermore, in the above steps, the mass ratio of NH3H2O, ethanol and tetraethyl silicate is 3:200:16. Preferably, the microwave mixing time after adding tetraethyl silicate is 3-7 minutes.

[0008] Preferably, the average particle size of the silica microsphere filler is 15-20 nm.

[0009] In a second aspect, a modified fluororubber is provided, which is prepared by mechanically blending silica microspheres as fillers with fluororubber, and the silica microspheres are prepared by the above-mentioned method for preparing silica microsphere fillers for fluororubber; specifically, the steps of mechanically blending silica microspheres as fillers with fluororubber include: fully mixing the silica microspheres in a double-roll mill, and then adding TAIC and bis(250)-1,2-dihydro-1,4-dimethylformamide in sequence, preparing vulcanized rubber after uniform mixing, and vulcanizing the vulcanized rubber to obtain a FKM / SiO2 composite material.

[0010] The beneficial effects of the present invention are as follows: the present invention adopts microwave mixing-Stober method to synthesize silica microspheres, and the prepared microspheres have a particle size of about 15-20nm. The microspheres are used as fillers and compounded with FKM to prepare FKM / SiO2 composite materials; after testing, the mechanical properties of the FKM / SiO2 composite material are significantly improved compared with those of the original FKM, and the tensile strength of FKM / SiO2-A4 is significantly improved (22MPa, an increase of 115%) compared with the original FKM; in summary, the synthesis of silica microspheres by microwave mixing-Stober method has broad application prospects in the field of high-performance FKM materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0012] Figure 1 Schematic diagram of the preparation of FKM / SiO2 composite materials;

[0013] Figure 2 TEM images of (a) SiO2-A2, (b) SiO2-A3, (c) SiO2-A4, and EDS mapping of O, Na, Si and P elements of (d) A4-SiO2;

[0014] Figure 3 (a) Tensile strength of FKM / SiO2 composites; (b) 100% and 300% tensile modulus of FKM / SiO2 composites; (c) Elongation at break of FKM / SiO2 composites, (d) Hardness of FKM / SiO2 composites; (e) Wear rate of FKM / SiO2 composites, (f) Permanent compression set of FKM / SiO2 composites;

[0015] Figure 4 SEM images of tensile fracture surfaces of FKM / SiO2 composites, (a) original FKM, (b) fluororubber with filler SiO2-A2, (c) fluororubber with filler SiO2-A3, (d) fluororubber with filler SiO2-A4;

[0016] Figure 5 TG curve (a), DTG curve (b), local enlarged view of DTG curve (c), and residual carbon rate (d) of FKM / SiO2 composite material;

[0017] Figure 6 Surface temperature changes of FKM / SiO2 composite materials: (a) temperature change curve over time during heating, (b) infrared image change diagram at intervals during heating, (c) temperature change curve over time during cooling, (d) infrared image change diagram at intervals during cooling. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0019] Material selection

[0020] FKM with 70% fluorine content was purchased from DuPont (Wilmington, USA). Tetraethyl silicate (TEOS) was purchased from Shanghai Myrel Biochemical Technology Co., Ltd. (Shanghai, China). Ammonium hydroxide (NH3H2O) was purchased from Sinopharm Chemical Reagent Co., Ltd. 2,5-Dimethyl-2,5-di(tert-butylperoxy)hexane (bis(2-5-nitropropene)) was provided by Yuyao Mingri Chemical Co., Ltd. (Yuyao, China). Triallyl isocyanurate (TAIC) was purchased from Rhein Chemie (Qingdao) Co., Ltd. (Qingdao, China).

[0021] Comparative Example 1 Preparation of Silica Microspheres by Mixing

[0022] First, dissolve 12 mL of 0.03 mol / L NH3H2O ​​in 200 mL of ethanol and stir for 10 min; add 16 mL of 0.0047 mol / L TEOS and stir for 24 h; centrifuge the resulting solution; place in an oven to dry to obtain SiO2-A2.

[0023] Comparative Example 2 Preparation of Silica Microspheres by Ultrasonic Mixing

[0024] First, dissolve 12 mL of 0.03 mol / L NH3H2O ​​in 200 mL of ethanol and stir for 10 min; add 16 mL of 0.0047 mol / L TEOS and mix ultrasonically for 2 h; centrifuge the resulting solution; place in an oven to dry, and obtain SiO2-A3.

[0025] Example 1 Preparation of Silica Microspheres by Microwave Mixing

[0026] First, dissolve 12 mL of 0.03 mol / L NH3H2O ​​in 200 mL of ethanol and stir for 10 min; add 16 mL of 0.0047 mol / L TEOS and mix in a microwave for 5 min; place the resulting sol in an oven to dry to obtain SiO2-A4.

[0027] Preparation of FKM / SiO2 composite materials

[0028] According to the formula in Table 1, FKM and SiO2-A2, SiO2-A3, and SiO2-A4 were fully mixed in a double-roll mill at 50°C. Then TAIC and bis(2-5-nitrogen) were added in sequence. Finally, the vulcanized rubber was prepared after uniform mixing, and the vulcanized rubber was post-vulcanized at 200°C for 24h to obtain the FKM / SiO2 composite material. The preparation process of the FKM / SiO2 composite material is as follows: Figure 1 .

[0029] Table 1 Raw material composition of FKM samples at different filler contents (phr).

[0030]

[0031] Test Case

[0032] 1. Morphological characterization of nanofillers

[0033] Figure 2 The TEM morphology of silicon dioxide prepared by different synthesis methods in Comparative Examples 1-2 and Example 1: (a), (b), and (c) are respectively silicon dioxide microspheres (SiO2-A2) obtained by mixing with a magnetic stirrer, silicon dioxide microspheres (SiO2-A3) obtained by ultrasonic mixing, and silicon dioxide microspheres (SiO2-A4) prepared by microwave mixing. According to Figures (a), (b), and (c), the average particle size of SiO2-A2 is 110-120nm, the average particle size of SiO2-A3 is 50-60nm, and the average particle size of SiO2-A4 is 15-20nm. It can be seen that the particle size of the silicon dioxide microspheres prepared by microwave mixing in Example 1 is smaller, Figure 2 (c) shows almost a single layer of silica spheres. The silanol groups on the surface of silica microspheres are agglomerated, but the silica particles synthesized by microwave assisted synthesis are small and have good dispersibility.

[0034] 2. Mechanical properties analysis of composite materials

[0035] Figure 3It is a test on the mechanical properties of composite materials, where A1, A2, A3 and A4 are FKM, FKM / SiO2-A2, FKM / SiO2-A3 and FKM / SiO2-A4 respectively. Figure 3 (a) is the tensile strength of the four composite materials. The tensile strengths of A1, A2, A3 and A4 are 10.23MPa, 21.07MPa, 20.20MPa and 22.00MPa respectively. The addition of silica microspheres significantly improves the tensile strength of the composite materials. SiO2-A4 has the smallest particle size and improves the tensile strength of the fluororubber composite materials most significantly. The small particle size filler obtained by microwave treatment enhances the cross-linking between it and the fluororubber molecular chain, making the interior of the fluororubber composite material more compact and improving the tensile strength of the composite material.

[0036] Figure 3 (b) is the tensile stress of the composite material at 100% and 300%. The tensile stress of A1, A2, A3, and A4 at a breaking elongation of 100% is 1.50MPa, 3.50MPa, 3.72MPa, and 3.90MPa, respectively; the tensile stress of A1, A2, A3, and A4 at a breaking elongation of 300% is 4.78MPa, 20.27MPa, 20.50MPa, and 20.24MPa, respectively. It can be seen that the addition of the silica microspheres prepared in Example 1 significantly improves the tensile strength of the composite material.

[0037] Figure 3 (c) is the elongation at break of the composite material. The elongations at break of A1, A2, A3 and A4 are 371.90%, 298.28%, 300.72% and 317.28%, respectively. Since the silica microspheres enhance the mechanical properties of the fluororubber composite material through mechanical riveting, the riveting surface between the large-particle silica and the fluororubber molecular chain is wider, and the tensile strength is significantly improved at the expense of the elongation at break. The silica prepared in Example 1 improves the tensile strength while improving the traditional method at the expense of the elongation at break.

[0038] Figure 3 (d) is the hardness of the composite material. The hardnesses of A1, A2, A3 and A4 are 59.50, 67.60, 67.1 and 71.4 respectively, indicating that the addition of silica microspheres improves the hardness of the composite material, and the improvement in Example 1 is obvious.

[0039] Figure 3(e) is the wear resistance of the composite material. The wear resistance of A1, A2, A3 and A4 are 53.94%, 103.50%, 96.28% and 98.22% respectively. It can be seen that the wear resistance of the original rubber is lower than that of the fluororubber composite material with added silica filler. This is because the added silica nanoparticles increase the surface roughness of the fluororubber composite material, and the surface is far less smooth than the original rubber. Because the wear amount is greatly increased, this also correspondingly proves that the addition of silica is embedded in the fluororubber molecules. Figure 3 (f) is the permanent compression deformation rate of the composite material. The permanent compression deformation rates of A1, A2, A3 and A4 are 82.18%, 30.26%, 32.43% and 39.27%, respectively. The addition of silica microspheres increases the permanent compression deformation rate of the fluororubber composite material and improves the compression deformation performance of the fluororubber composite material.

[0040] The microstructure of the composite material was analyzed by SEM. Figure 4 shown. Figure 4 (a) It can be observed that the original FKM surface is smooth, part of the rubber matrix is ​​pulled out, and the tensile strength of the composite material is relatively low. Figure 4 (b) The addition of filler SiO2-A2 exposes a large amount of SiO2 nanofillers directly on the rubber surface and disperses them evenly, increasing the surface roughness and enhancing the mechanical riveting effect between the nanofillers and the rubber matrix, further confirming the enhancement of the tensile strength of the composite material A2. Figure 4 (c) With the addition of filler SiO2-A3, some silica microspheres agglomerated on the surface of the rubber matrix, exposing a large amount of SiO2 nanofillers directly on the rubber surface, making the tensile strength enhancement of composite material A3 slightly lower than that of A2. Figure 4 (d), with the addition of filler SiO2-A4, the silica microspheres are well fused on the surface of the rubber matrix, and the surface of the rubber matrix is ​​smooth with cracks, indicating that the interface connection is enhanced, and some SiO2 nanofiller particles are agglomerated, which further confirms the enhancement of the tensile strength of the composite material A4.

[0041] 3 Thermal performance analysis of composite materials

[0042] Figure 5 They are TG curve, DTG curve and carbon residue rate of the composite material respectively. Figure 5 (a) is the thermogravimetric (TG) curve of the modified fluororubber, where the decomposition peak represents the decomposition of the rubber component, mainly the thermal decomposition of the FKM side groups and the CC bonds on the main chain. The thermal decomposition process of the composite materials A1, A2, A3 and A4 is completed between 400 and 500 °C. Figure 5In (b) and (c), the addition of silica microspheres increases the maximum decomposition temperature of the composite materials. The maximum decomposition temperatures of FKM / SiO2-A2 and FKM / SiO2-A4 are higher than those of FKM and FKM / SiO2-A3.

[0043] Figure 5 (d) is the carbon residue rate of the composite material. The carbon residue rates of the composite materials A1, A2, A3 and A4 are 6.61%, 9.74%, 9.99% and 15.02% respectively. After adding silica microspheres, the carbon residue rate of the composite material is improved. Figure 6 The infrared thermal imager captures the temperature change of the composite material over time during the heating or cooling process of the fluororubber composite material. Figure 6 (a) and (b) are the temperature changes of the composite materials with time during heating, and (c) and (d) are the temperature changes of the composite materials with temperature during cooling. The darker the color, the lower the temperature, and the lighter the color, the higher the temperature. It can be found that the heating rate and cooling rate of the composite materials with added silica filler are higher than those of the original rubber. The addition of silica filler can improve the thermal properties of fluororubber composite materials. When the heating time reaches 100s, the peak temperatures of A1, A2, A3 and A4 composite materials are 85.1, 89.3, 89.0, and 86.5℃ respectively; when the cooling time reaches 100s, the peak temperatures of A1, A2, A3 and A4 composite materials are 68.6, 62.0, 60.0, and 60.0℃ respectively; the addition of silica filler improves the thermal properties of the composite materials, with better heating rate and cooling rate. The decrease in the peak temperature of SiO2-A4 composite material may be due to its less thermal barrier.

[0044] In summary, the present invention adopts the microwave mixing-Stober method to synthesize silica microspheres as fillers for fluororubber, which not only greatly saves the preparation time of the silica microsphere filler, but also improves the performance of the fluororubber prepared by using the silica microsphere filler. The improved effect cannot be simply predicted by microwave mixing, but has a beneficial effect that is difficult to directly predict. For example, the tensile strength of the original FKM is 10.23 MPa, and the tensile strength of the fluororubber prepared by using the silica microsphere filler is significantly improved (22 MPa, an increase of 115%).

[0045] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for synthesizing silica microsphere filler for fluororubber, characterized in that: The preparation method of the silica microsphere filler comprises: dissolving NH3H2O ​​in ethanol and stirring evenly, then adding tetraethyl silicate and mixing by microwave to obtain a sol, and drying the obtained sol to obtain the silica microsphere filler.

2. The method for synthesizing a silica microsphere filler for fluororubber according to claim 1, characterized in that: The mass ratio of NH3H2O, ethanol and tetraethyl silicate is 3:200:

16.

3. The method for synthesizing a silica microsphere filler for fluororubber according to claim 1, characterized in that: NH3H2O ​​was dissolved in ethanol and stirred evenly, and then tetraethyl silicate was added and the mixing time in microwave was 3-7 minutes.

4. The method for synthesizing a silica microsphere filler for fluororubber according to claim 1, characterized in that: The average particle size of the silica microsphere filler is 15-20 nm.

5. A modified fluororubber, prepared by mechanically blending silica microspheres as fillers with fluororubber, wherein the silica microspheres are prepared by the synthesis method of silica microsphere fillers for fluororubber as claimed in any one of claims 1 to 4.

6. The modified fluororubber according to claim 5, characterized in that: The steps of mechanically blending silica microspheres as fillers with fluororubber include: fully mixing the silica microspheres in a double-roll mill, then adding TAIC and bis(250)-1,5-dihydro ...